Burkholderia pseudomallei Isolates from Sarawak Malaysian Borneo Are Predominantly Susceptible to Aminoglycosides and Macrolides - Yuwana, Podin; Sarovich, Derek S.; Price, Erin P.; Kaestli, Mirjam; Mayo, Mark; Hii, King Ching; Ngian, Hie Ung; Wong, See Chang; Wong, Ing Tien; Wong, Jin Shyan; Mohan, Anand; Ooi, Mong How; et al. (American Society for Microbiology., 2013)
Melioidosis is a potentially fatal disease caused by the saprophytic bacterium Burkholderia pseudomallei. Resistance to gentamicin is generally a hallmark of B. pseudomallei, and gentamicin is a selective agent in media used for diagnosis of melioidosis. In this study, we determined the prevalence and mechanism of gentamicin susceptibility found in B. pseudomallei isolates from Sarawak, Malaysian Borneo. We performed multilocus sequence typing and antibiotic susceptibility testing on 44 B. pseudomallei clinical isolates from melioidosis patients in Sarawak district hospitals. Whole-genome sequencing was used to identify the mechanism of gentamicin susceptibility. A novel allelic-specific PCR was designed to differentiate gentamicin-sensitive isolates from wild-type B. pseudomallei. A reversion assay was performed to confirm the involvement of this mechanism in gentamicin susceptibility. A substantial proportion (86%) of B. pseudomallei clinical isolates in Sarawak, Malaysian Borneo, were found to be susceptible to the aminoglycoside gentamicin, a rare occurrence in other regions where B. pseudomallei is endemic. Gentamicin sensitivity was restricted to genetically related strains belonging to sequence type 881 or its single-locus variant, sequence type 997. Whole-genome sequencing identified a novel nonsynonymous mutation within amrB, encoding an essential component of the AmrAB-OprA multidrug efflux pump. We confirmed the role of this mutation in conferring aminoglycoside and macrolide sensitivity by reversion of this mutation to the wild-type sequence. Our study demonstrates that alternative B. pseudomallei selective media without gentamicin are needed for accurate melioidosis laboratory diagnosis in Sarawak. This finding may also have implications for environmental sampling of other locations to test for B. pseudomallei endemicity.